OneOp: A Professional Development Resource for Extension Professionals - Kristen Jowers; Martie Gillen (EDIS, 2023)
This publication is part of a series that aims to provide valuable resources, information, and support to family service professionals and Extension agents who support military families navigating the unique challenges and opportunities that come with a military lifestyle. Written by Kristen Jowers and Martie Gillen, and published by the UF/IFAS Department of Family, Youth and Community Sciences, July 2023.